Male Germline Chromatin - Griffin, Darren; Ellis, Peter (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Spermatogenesis requires radical restructuring of germline chromatin at multiple stages, involving coordinated waves of DNA methylation/demethylation, histone modification, and the replacement and removal that occurs before, during, and after meiosis. This Special Issue will draw together papers that address all aspects of chromatin organization and dynamics in the male germ line, in humans, and in model organisms. In particular, we will invite authors to discuss novel methods for studying germline chromatin structure, the interplay between chromatin structure and susceptibility to DNA damage and mutation, chromatin modifications associated with epigenetic inheritance in the early embryo, and the impact this work has for understanding natural fertility and improving assisted reproduction techniques.